Analisis Pembebanan Terhadap Perkiraan Umur Transformator Distribusi 20 kV Penyulang Lowokwaru di PT. PLN(PERSERO) UP3 Malang - Asfari Hariz Santoso; Ernanda Rizka; Harrij Mukti K. (Politeknik Negeri Malang, 2022)
One of the causes of the reduced life of the transformer is due to loading. From the eleven transformers, it can be seen that there are different loading variations, it is expected that the transformer life will remain at normal age. IEC 60354-1, 1991 stipulates the normal life of the transformer is 20.55 years. The research method used is to perform calculations using the long-time method and 24-hour daily data by calculating the loading at the time of LWBP and WBP on a 20 kV distribution transformer. Analysis of the calculation results revealed that the normal condition of the transformer P1385 (68.66 %) winding temperature at LWBP 67.47°C and when WBP 69.45°C compared to transformer P0032 with overload conditions (120.91%) winding temperature when LWBP 60, 88°C and at WBP 119.51°C. From the data on the lowest loading on the eleven transformers, namely transformer P0527 (41.69%) it is obtained that the estimated real aging age is 0.125 and the estimated age of the P0527 transformer is >20 years. Compared to transformer P0032 (120.91%), the estimated real aging age is 12,0003 p-u and the estimated age is less than 20 years or 9.5 years. Loading above 100% on the transformer based on the standard IEC 60354-1, 1991 if it takes place continuously will cause heating of the transformer windings which can cause the shrinkage process in the life of the transformer to be faster.